Collaborative Governance in Strengthening Dimensions of Competitive Advantage of Sustainable Ecotourism Villages - Purnamawati, I Gusti Ayu; Hatane, Saarce Elyse (International Review of Management and Marketing, 2024)
This study reveals the collaborative governance roles in strengthening the competitive advantage of sustainable ecotourism villages with three dimensions as moderating variables. The research used an explanatory approach with research locations conducted in 50 tourist villages in Buleleng Regency, Bali Province. The research data were collected using a questionnaire with a Likert scale. Respondents in this study were village heads, BUMDES managers, pokdarwis, customary chiefs, and the community, so the research sample totaled 250 people. Data were analyzed using the Structural Equation Modeling model using WarpPLS 5.0. The research results show the transparency and accountability variables, have a positive and significant effect on sustainable ecotourism villages, while the responsibility variable shows different results. Likewise, the three dimensions of the village can moderate the effect of transparency and responsibility on sustainable ecotourism villages. In comparison, the three dimensions of the village cannot moderate the impact of accountability on sustainable ecotourism villages.